Association of Urinary Neutrophil Gelatinase-Associated Lipocalin With Long-Term Renal Outcomes in ICU Survivors: A Retrospective Observational Cohort Study. Issue 1 (July 2016) - Isshiki, Rei; Asada, Toshifumi; Sato, Dai; Sumida, Maki; Hamasaki, Yoshifumi; Inokuchi, Ryota; Matsubara, Takehiro; Ishii, Takeshi; Yahagi, Naoki; Nangaku, Masaomi; Noiri, Eisei; Doi, Kent
ABSTRACT: Background: Epidemiological studies recently suggested that acute kidney injury (AKI) in intensive care units (ICUs) increases the risk of chronic kidney disease development and progression. However, whether any AKI biomarker can predict long-term renal outcomes in ICU survivors remains unclear. This study was undertaken to elucidate the role of urinary biomarkers for long-term renal outcome prediction after ICU discharge. Methods: This retrospective observational study examined 495 adult patients who had been admitted to the ICU of the University of Tokyo Hospital. Major adverse kidney events (MAKE): death, incident end-stage renal disease (ESRD), and halving of estimated glomerular filtration rate (eGFR), at hospital discharge and long-term renal outcomes of 30% reduction of eGFR or incident ESRD were evaluated. Results: Among all the enrolled 495 patients, 393 patients were discharged from the hospital without MAKE. Data of eGFR up to two years after ICU discharge were available for 173 patients; 63 patients (36.4%) were positive for long-term renal outcomes. Step-wise logistic regression analysis demonstrated that male sex and urinary neutrophil gelatinase-associated lipocalin (NGAL) measured at ICU admission showed significant associations with long-term renal outcomes. Receiver operating characteristic curve analysis showed the area under the curve of 0.66 (95% confidence interval 0.57–0.74) for prediction of long-term renal outcome by urinary NGAL. Conclusion: Urinary NGAL measured at ICU admission was significantly associated with long-term renal outcomes after hospital discharge in MAKE-free ICU survivors. Urinary NGAL measurements at ICU might be useful to identify a high risk population of kidney disease progression after intensive care. Abstract : Supplemental Digital Content is available in the text